Hematopoietic stem cell transplant in peru: experience and challenges of the largest transplant center in Perú: Trasplante de células madre hematopoyéticas en el Perú: experiencia y desafíos del centro de trasplante más grande del Perú - Aranda-Gomero, Lourdes (2022)
Bone marrow transplantation, currently known as hematopoietic stem cell transplant (HSCT), involves the infusion of stem cells healthy hematopoietic cells to patients with dysfunctional bone marrow, diminished or compromised by hematological neoplasms. Since its rst exploration in humans in the 1950s based on the results obtained in animal models, more than one million procedures have now been performed in Europe and collaborating countries. Early detection of complications and histocompatibility typing (HLA) with which potential donors can be better-selected thanks to an international donor registry network of bone marrow and the advancement of technology in terms of support treatment.